(3JMUjd GdefG aj TQM JdNjU GHf GdHfGs - (3jYbhHs ((3YHO Gddg Hf YHO GdQMef GdOhYji s)
(3ChdgG (B:s
(3hHYO aEfi bQCJ cJGH GdJdNjU dGHf GdHfG ai SfI NeS hNeSjf hSHYeGFg s
(3BNQgG (B:s
(3ced cJGH JMUjd GdUfGYg s
(3Vef eLehY , JQJjHgG (B: (3GdChds
(3eUOQ GbJfGA GdCUd (B:s
(3GdRGhjI GdMeRGhjI (B- (3GdeZQH (B(145) s
Keywords: (3GdQjGVjGJs